A retrospective study of non-insulated microneedle radiofrequency on wrinkles of facial photoaging subjects - Anwer, Wedad; Sun, Yan; Wang, Bin; Wu, Yan; Xiao, Bihuan (Lasers in medical science, 2024)
Non-insulated microneedle radiofrequency (NIMNRF) is a method of promoting dermal collagen shrinking and remodeling with minor injury reducing wrinkles. We conducted a 3-years retrospective observation on wrinkles of facial photoaging subjects treated with NIMNRF in Chinese subjects to demonstrate the efficacy and side effects. Chinese subjects clinically diagnosed as facial photoaging treated with MNRF in the Laser Center of The First Hospital of China Medical University and Guangzhou Mylike Medical Cosmetic Hospital from Jan 1, 2018 to Dec 31, 2021 were enrolled in this study. Inclusion criteria included. Each subject was treated with NIMNRF for 1–3 sessions, with a 3-month interval. At baseline and 3 months after each treatment, a Wrinkle Assessment Scale (WAS) was used to score the wrinkles in 10 areas. The total WAS score and WAS improvement rate was assessed at each time point. A total of 96 subjects, aged 25–65 years old, received at least one session of NIMNRF were enrolled. 63, 24, 9 of them received 1, 2 or 3 sessions, respectively. The total WAS score decreased from 14.65 ± 9.20 to 11.51 ± 8.70 after Session 1, from 15.92 ± 9.48 to 12.17 ± 8.83 after Session 2 and from 17.56 ± 6.99 to 11.11 ± 7.13 after Session 3 ( P < 0.01). The WAS improvement rate was 25.61%, 30.69% and 39.82% after 1, 2, 3 sessions, respectively. As for subjects in different age groups, the improvement rate decreased with age, from 39.13% in 25–30 years old group to 16.39% in over 60 years old group after Session 1 ( P < 0.05). Better efficacy and less sessions of treatments were conducted in younger subjects. NIMNRF can be used in the treatment of facial wrinkles in photoaging subjects, especially in youngster as better efficacy.